Perlindungan Hukum terhadap Anak sebagai Korban Pelecehan Seksual di Wilayah Polrestabes Medan - Zulamin Ginting; Rasina Padeni Nasution (Verdict: Journal of Law Science, 2026)
Legal protection for children who are victims of sexual abuse is a state obligation that focuses not only on prosecuting perpetrators but also on upholding victims' rights and facilitating their recovery. Although child protection is mandated by Law Number 35 of 2014 concerning Child Protection, its implementation in the field faces various obstacles. This study aims to analyze the implementation of legal protection for child victims of sexual abuse within the jurisdiction of the Medan City Police (Polrestabes Medan), identify the challenges involved, and formulate strategic solutions to enhance the effectiveness of legal protection for victims. The study employs an empirical-juridical method with a qualitative descriptive approach. Data were collected through interviews, observation, and document analysis, and subsequently analyzed qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that legal protection measures have been implemented, including report intake, child-friendly questioning, investigation, victim support, identity confidentiality, coordination with relevant agencies (such as DP3A, UPTD PPA, hospitals, psychologists, and other institutions), as well as victim rehabilitation and recovery. However, implementation remains suboptimal due to challenges such as victims' reluctance to open up, limited evidence, inconsistencies in victims' statements, and a lack of optimal coordination during the rehabilitation and recovery processes. Therefore, it is necessary to strengthen child-friendly questioning procedures, multidisciplinary approaches to evidence gathering, inter-agency synergy, public and family education, and the capacity building of law enforcement officers. This study underscores the importance of integrated protection through preventive, repressive, and restorative approaches.